Peran Program Maghrib Mengaji dalam Mengurangi Aktivitas Negatif Anak di Desa Ujung Negeri Kahan - Fauziah Nasution; Rahmi Aulia; Siti Khairuna Salwa Lubis; M. Iqbal Ritonga; Sofi Mayla Humairah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The phenomenon of moral degradation and the increase in negative activities among children during the crucial hours between dusk and evening have become serious challenges for the community in Ujung Negeri Kahan Village. This community service research aims to evaluate and optimize the role of the "Maghrib Mengaji" program as a preventive instrument to shield children from unhealthy environmental influences and gadget dependency. The method employed in this service is participatory mentoring using the Asset-Based Community Development (ABCD) approach, involving religious leaders, parents, and village officials. Through the restructuring of activities in mosques and prayer rooms, this program focuses not only on Qur'anic literacy but also on the cultivation of noble character (akhlakul karimah). The results indicate a significant transformation in behavior; children who previously engaged in counterproductive outdoor activities are now more focused on positive spiritual and social endeavors. The success of the program is indicated by a decrease in the intensity of nighttime wandering and an increase in learning discipline. The conclusion of this activity confirms that community synergy through structured religious programs is effective in reducing the potential for juvenile delinquency and strengthening the moral resilience of the younger generation at the rural level.